Investigation on antigen-specific T-cell responses induced by outer membrane vesicles from Escherichia coli Δ60 strain - Tomasi, Michele; Croia, Lorenzo; Zanella, Ilaria; Gagliardi, Assunta; Boscato Sopetto, Giulia; Benedet, Mattia; Di Lascio, Gabriele; Gambini, Gaia; Berti, Alvise; Corbellari, Riccardo; Grandi, Guido; Grandi, Alberto (Frontiers in Immunology, 2025)
There is a growing interest in the exploitation of bacterial outer membrane vesicles (OMVs) for the design of vaccines and novel antitumor immunotherapeutic products. Such interest is motivated by their potent immunostimulatory properties, which promote elevated immune responses against heterologous antigens combined with OMVs by genetic engineering, chemical coupling, or absorption. However, for a full exploitation of OMVs, a few questions remain to be fully addressed: what is the appropriate ratio of OMVs/heterologous antigen needed to obtain an optimal antigen-specific immune response? To what extent do OMV endogenous proteins interfere with or favor antigen-specific immunity? Using OMVs derived from our Escherichia coli Δ60 (E. coli Δ60) strain, we recently addressed these questions, focusing on the humoral immune responses, and we determined the concentrations of the OMV-associated proteins necessary and sufficient to elicit saturating levels of specific antibodies. In this work, we focused on cell-mediated immunity. We show that, because of the numerous OMV-associated MHC II epitopes, OMV immunization elicited detectable levels of IFN-γ+ epitope-specific CD4+ T cells provided that epitope concentrations were >10% of the total OMV proteins (w/w). Such elevated concentrations could be achieved by mixing synthetic peptides with OMVs but not by genetic manipulation of OMVs. By contrast, most likely thanks to the cross- help of the polyclonal CD4+ T cell population, elevated frequencies of epitope-specific CD8+ T cells were found even when MHC I epitopes were present at concentrations lower than 1% of the total OMV proteins. Our data provide a mechanistic insight of the OMV-mediated immune responses and have important implication in vaccine design.